New Trends in Israel Regional Policy (2009-2019) - T. A. Karasova (Vestnik MGIMO-Universiteta, 2019)
Changes in Israeli regional politics were triggered by the current political situation in the Middle East, characterized by a high degree of intensity and unpredictability. The region experiences a complex process of serious political changes making Israel adjust its regional policy to the new challenges. The article focuses upon the new elements of Israelis strategy on key regional issues: the settlement of Palestinian-Israeli conflict; new approaches to countering Iranian nuclear program; the Syrian civil war and escalation of terrorism activities. The aim of the article is to describe and analyze new trends in Israeli regional strategy over the past 10 years identifying its external and internal factors. The main external factor is a close partnership of Israel with US, which plays a key role in supporting Israel’s regional and international status. The changes taking place inside the region could be considered as internal factors. They include Arab Spring; prospects for settlement of the Palestinian-Israeli conflict; the growth of the Islamic radicalism and terrorism, new terrorist groups such as ISIS, and the civil war in Syria.The main changes of Israeli regional policy include toughening approaches to resolving the Palestinian-Israeli conflict, in particular, de facto abandonment of the «two states for two peoples» formula. Equally important are events that, although not directly related to Israel, are changing its regional agenda. Assessment of Iran’s nuclear program as an existential threat explains Israel’s negative attitude to the international agreement with Iran in 2015 during the presidency of B. Obama (JCPOA). The subsequent withdrawal of the Trump administration from this agreement strengthened Israel’s anti-Iranian position. This also allowed Israel to develop cooperative ties with the so-called pro-Western states of the region, such as Saudi Arabia and some Persian Gulf countries in pursuit of containing the Iranian nuclear threat and its growing regional influence. Saudi Arabia and the Gulf countries became real partners of Israel in confronting Iran. This gives the Israeli state the opportunity to at last enter the regional system and free itself from the traditional image of rogue state among the Muslim countries in the Middle East.